Mineral Composition of Some Important Indigenous Savanna Forage Shrub Species in Ghana - Ziblim Abukari Imoro; Danquah Emmanuel; Ammal Abukari (Turkish Journal of Agriculture: Food Science and Technology)
This study compared the forage quality of Cajanus cajan, Stylosanthes mucronata, Tephrosia purpurea, and Securinega virosa in the savanna ecological zone of Ghana. The shrubs were cultivated using Randomized Complete Block Design (RCBD) and their growth were monitored. Leaf samples were hand-harvested at 7, 10, and 13 weeks after establishment, air-dried, pulverised, and used for laboratory analysis. Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca), and Magnesium (Mg) were determined. N, P, K, Ca and Mg contents among the shrubs ranged from 0.74 - 0.79%, 1.32 - 1.99%, 7.63 - 10.09%, 2.22 - 3.06 and 1.08 - 1.38%, respectively. Stylosanthes mucronata was significantly lowest in both P (1.318%) and K (7.63%), whilst Securinega virosa was significantly highest in K (10.09%). Among the three maturity levels, N, P, K, Ca and Mg contents ranged from 0.31 – 1.05%, 1.51 - 1.93%, 7.46 - 10.43%, 2.63 - 2.67% and 1.28 - 1.30%, respectively. Except for P, which was significantly lowest at 10 weeks after establishment (WAE), N and K were significantly highest at 7 WAE and lowest at 10 and 13 WAE, respectively. It was observed that the shrub species and maturity levels influence the nutrient content of forage shrubs.